The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1055/a-2127-7880
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-PSMA-1007-PET for evaluation of kidney function

Philipp Rassek,
Michael Schäfers,
Kambiz Rahbar
et al.

Abstract: Purpose Prostate-specific membrane antigen (PSMA) is present in the proximal tubule cells of the kidneys. This results in high renal tracer uptake in PSMA-PET, which may contain useful information on renal function. As part of the evaluation for [177Lu]-PSMA therapies, patients undergo PSMA-PET and additional [99mTc]-mercapto-acetyltriglycine (MAG3) scintigraphy to assess renal function. Aim of this study was to evaluate estimation of renal function with [18F]-PSMA-1007-PET/CT (PSMA-PET) by comparison to timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…This suggests that 68 Ga-PSMA-derived split function can serve as a reliable alternative for assessing functional renal tissue. Our findings are in agreement with previously published data which showed a positive correlation between SRF derived by 68 GaPSMA PET and 99m Tc-MAG3 scintigraphy as shown in Table 3 [ 25 , 26 , 27 , 28 ]. In a study by Rassek et al, SRF MAG3 was strongly correlated with SRF PSMA (r = 0.872, p < 0.001) [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This suggests that 68 Ga-PSMA-derived split function can serve as a reliable alternative for assessing functional renal tissue. Our findings are in agreement with previously published data which showed a positive correlation between SRF derived by 68 GaPSMA PET and 99m Tc-MAG3 scintigraphy as shown in Table 3 [ 25 , 26 , 27 , 28 ]. In a study by Rassek et al, SRF MAG3 was strongly correlated with SRF PSMA (r = 0.872, p < 0.001) [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is similar to the findings of a recent study by Rosar et al, who depicted reno-ureteral obstruction by PSMA PET/CT imaging in most cases (92.9%) [ 29 ]. A study by Rassek et al also demonstrated that relevant abnormalities of SRF MAG3 could be detected with sensitivities and specificities of 90% and 92% for SRF PSMA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But even if the intensity of [ 68 Ga]Ga-PSMA-11 uptake does not depict glomerular kidney function, conclusions on local impairments of kidney function or loss of function of a single kidney might be drawn. Also, regarding the assessment of partial kidney function, PSMA ligand PET/CT showed comparable results with standard techniques like [ 99m Tc]Tc-DMSA or [ 99m Tc]Tc-MAG3 scintigraphy [16,37,43].…”
Section: Results and Comparison To The Literaturementioning
confidence: 78%
“…The best correlation was found by these authors using the product of SUV mean and segmented volume, similar to the TRCU used in this study, which had less dependence than segmented volume in our data. In contrast, other studies investigated poor correlations between renal [ 18 F]PSMA-1007 uptake and eGFR [37]. Moreover, the [ 18 F]PSMA-1007 uptake within the bladder also showed no correlation with kidney function [38].…”
Section: Results and Comparison To The Literaturementioning
confidence: 90%